On-field Raman spectroscopy of Patagonian prehistoric rock art: Pigments, alteration products and substrata - Rousaki, Anastasia (2018)
An extensive in situ Raman spectroscopic campaign was performed on archaeological sites in three different provinces in Patagonia, Argentina (Neuquén, Río Negro and Chubut). 16 open air shelters located in different environments (forests, ecotones, steppes) were investigated and interpreted in terms of pigments used and the identification of substrata. Special attention was given to the alteration products and accretions that were found on the rock art paintings of the shelters and on the surface of the rock walls, as they can affect and damage this magnificent works of art. Haematite (α-Fe2O3) was the main chromophore that was found on the red paintings of the most of the shelters studied. The green earth glauconite, was identified only in one case, by using a red (785 nm) and a green laser (532 nm). Other minerals and silicates were found on the coloured areas but also on the rock support. Calcite (CaCO3) and gypsum (CaSO4 • 2H2O) crystallization was identified on the paintings, crusts and rock surfaces, in combination or alone, and are associated with weathering. In some cases the shelters were so severely degraded that no Raman signal of pigments and/or other components could be retrieved. Calcium oxalates were also detected in several figures and motifs in different shelters.